A highly sensitive probe based on spiropyran for colorimetric and fluorescent detection of thiophenol in aqueous media. (April 2020) - Yang, Linlin; Li, Yanping; Song, Huaxiong; Zhang, Haihua; Yang, Nan; Peng, Qian; Ji, Liguo; He, Guangjie
Abstract: A novel spiropyran-based colorimetric probe SP-DNP bearing a 2, 4-dinitrophenyl group as a PhSH-responsive site was synthesized for the detection of thiophenol based on the ring open/closed isomerization process. Upon the addition of PhSH, the probe SP-DNP displayed a remarkable change in UV–vis spectra with a good linear relationship to concentration of PhSH, and result in apparent color change from purple to colorless that could be easily observed by the naked eye even in the presence of other interfering anions. Probe SP-DNP exhibited specific colorimetric response toward PhSH with very fast response (within 30 s) and high sensitivity (detection limit is 0.55 μM). In addition, the probe showed good selectivity and sensitivity toward PhSH through fluorescence quenching process. The sensing mechanism of the nucleophilic substitution-cyclization process was confirmed by 1 H NMR and mass spectroscopic analysis. Moreover, probe SP-DNP could detect PhSH in real water samples. Graphical abstract: Image 1 Highlights: Probe SP-DNP was constructed on basis of thiophenol-induced transform merocyanine to spiropyran isomerization process. The probe could colorimetric and fluorescent respond toward thiophenol with fast response and high sensitivity. The probe has been successfully demonstrated in monitoring thiophenol in real water samples.